PENGEMBANGAN MEDIA FLASHCARD BERBANTUAN AUGMENTED REALITY DALAM MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN IPAS - Dwi Putri Diani; Desi Wulandari (Jurnal Penelitian Pendidikan IPA, 2025)
The low learning outcomes of science material on the Human Respiratory System and the lack of application of learning media in the learning process are certainly a complex problem in science learning in elementary schools. The purpose of this study was to determine the development design, feasibility, and effectiveness of media Flashcard assisted by Augmented Reality for grade V students of SDN 01 Kajen. This research is a Development and Research (R&D) with the ADDIE development model, which consists of five stages namely analysis, design, development, implementation, and evaluation. The results of this study indicate that media Flashcard assisted by Augmented Reality is suitable for use in elementary schools. The results of material validation showed an average value of 90% with the category “Very Feasible”, while the results of media validation obtained an average value of 96% with the same category. The use of media Flashcard assisted by Augmented Reality proved effective in improving IPAS learning outcomes on Human Respiratory System material with the percentage of posttest reaching 85.68%, while the pretest only reached 50.00%.